BODY IMAGE AND SOCIAL ANXIETY OF OBESE YOUNG WOMEN - Sarita Fajar Andini; Hamidah Hamidah (Universitas Mercu Buana Jakarta, 2022)
The aim of this study is to find out the correlation between body image and social anxiety in obese adolescent girls. Adolescent girls who are obese will tend to experience social anxiety because of the negative body image that appears in them. The study was conducted on 129 obese adolescent girls aged 12-21 years old. The data was collected using a questionnaire of MBSRQ-AS (Multidimensional Body-Self Relations Questionnaire-Appearance Scales) and Social Anxiety Scale for Adolescent (SAS-A). The data was analyzed by Spearman's Rho using IBM SPSS Statistics 22.0 for Mac. The result showed that social anxiety has significant negative correlation with appearance evaluation (ρ = 0,000 r=-0,462), body area satisfaction (ρ = 0,000 r=-0,415), and self-classified weight (ρ = 0.004 r=-0,252). However, there is a positive significant correlation between social anxiety and overweight preoccupation with the level of significance ρ = 0,024 and correlation coefficient is 0,199. Therefore, there is no correlation between appearance orientation with social anxiety because the level of significance is 0,995.